Karakter Perempuan Generasi Digital Native Melawan Berita Hoax dalam Pendidikan Agama Islam - Maghfirotun, Khubni (Fakultas Agama Islam Universitas Billfath, 2023)
This study aims to describe the way female students of Al Fattah Tarbiyah College of Science fight hoax news circulating on social media accounts owned by students and analyze the contributions that have been made to prevent hoax news from spreading. This research is qualitative descriptive. This type of research is a case study. The source of the data was obtained from interviews with all female students regarding ways and strategies to fight hoax news on social media. The data collection technique used is through observation and interviews. The analysis used in this study is the Miles Huberman Theory. Based on this research, female students fight hoax news in the following ways; 1) Analyze news by reading titles carefully, Comparing news from one media to another, Checking the veracity of photos, Checking website addresses, Reading the whole news, and Rereading the news that appears repeatedly 2) Strengthen character with literacy education, critical thinking and logical thinking 3) Determine attitudes by initiating control Attitude, do not forward news, activate the report site and block news.